2017
DOI: 10.4018/978-1-5225-2229-4.ch048
|View full text |Cite
|
Sign up to set email alerts
|

Designing Multilayer Feedforward Neural Networks Using Multi-Verse Optimizer

Abstract: Artificial neural network (ANN) models are involved in many applications because of its great computational capabilities. Training of multi-layer perceptron (MLP) is the most challenging problem during the network preparation. Many techniques have been introduced to alleviate this problem. Back-propagation algorithm is a powerful technique to train multilayer feedforward ANN. However, it suffers from the local minima drawback. Recently, meta-heuristic methods have introduced to train MLP like Genetic Algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Comparative analysis of the results showed that MVO outperformed PSO, GA, DE, firefly, and CS optimization algorithms. In related work, Hassanin and colleagues 79 discussed how to optimize multilayer feedforward neural networks using MVO. Another interesting work was presented by Hossam and colleagues, 80 who proposed the use of MVO for performance tuning of the parameters of SVM while simultaneously selecting optimal features.…”
Section: Metaheuristic Algorithms and Related Workmentioning
confidence: 99%
“…Comparative analysis of the results showed that MVO outperformed PSO, GA, DE, firefly, and CS optimization algorithms. In related work, Hassanin and colleagues 79 discussed how to optimize multilayer feedforward neural networks using MVO. Another interesting work was presented by Hossam and colleagues, 80 who proposed the use of MVO for performance tuning of the parameters of SVM while simultaneously selecting optimal features.…”
Section: Metaheuristic Algorithms and Related Workmentioning
confidence: 99%
“…The multiverse optimizer (MVO) algorithm has also been widely used in different fields. In References [40,41], MVOs were used to train multilayer perceptron neural networks. Benmessahel [42] combined the MVO and the artificial neutral network to develop an intrusion detection system.…”
Section: Introductionmentioning
confidence: 99%